Resistor-transistor logic circuits using vertical-type organic transistors. (12th April 2016) - Agatsuma, T.; Muto, H.; Nakayama, K.
ABSTRACT: NOR gate operation using organic devices was demonstrated based on resistor-transistor logic (RTL). The RTL was composed of an OR gate using two single layered devices as input resistors and a NOT gate (inverter) using a vertical-type metal base organic transistor (MBOT). The input resistors were connected to the base electrode of the MBOT. When either input was turned from low to high voltage, the output voltage changed from high to low, indicating NOR operation. Dynamic characteristics of the RTL circuit was also evaluated, and operation frequency was estimated to be 300 Hz.